Viva Madiba, Viva ! - Myriam Houssay-Holzschuch (EchoGéo)
This short paper synthetizes Nelson Mandela's biography on the occasion of his 90th birthday. It retraces his formative years, his entry into politics and activism, his imprisonment by the apartheid regime, his triumphant liberation and his election as the first democratically elected president of South Africa. It shows how Mandela has been able to draw on various political traditions and Weberian types of domination. He embodied the anti-apartheid struggle, and has become a global icon.